Determinação de resíduos e contaminantes em rações empregando extração sólido-líquido e UHPLC-MS/MS - Ribeiro, Lucila Cendon (2022)
Animal feed is considered as any material of vegetable, animal or mineral origin suitable to be consumed as food, provided it meets the quality and identity standards, as well as sanitary and nutritional standards. Also included are products from industries (derivatives), with or without additives. These substances, as well as veterinary drugs, must be used properly, ensuring the health of humans, animals, and the environment. In addition, pesticides can be present in feed from the raw materials used in production. Therefore, the objective of this study was to develop a method for the determination of 182 additives, residues and contaminants in poultry and swine feeds using a simple and rapid sample preparation method and ultra-high performance liquid chromatography coupled to serial mass spectrometry (UHPLC-MS/MS). A 2 g sample was used, followed by a hydration step and extraction with acetonitrile and trichloroacetic acid. The obtained extract was percolated onto an SPE cartridge containing EMR-Lipid®. An aliquot was diluted 5 times in ultrapure water for analysis by UHPLC-MS/MS using Xevo TQ-XS equipment (Waters, USA). The chromatographic separation was performed on an Acquity UPLCTM HSS T3 column (100 × 2.1 mm i.d.; 1.8 μm), mobile phase A: ultrapure water and B: acetonitrile, both with 0.05% (v/v) formic acid, and constant flow rate of 0.35 mL min-1 . The injection volume was 10 µL. The electrospray ionization (ESI) source operated in positive and negative mode. Analytical curves were prepared in solvent and matrix white extract at levels between 5 and 640 µg kg-1, and coefficients of determination (r2 ) > 0.99 were obtained for most compounds. The lowest calibration levels (LCL) 5; 10; 20 and 80 µg kg-1 , as well as 1x, 2x and 3x these values were evaluated for the compounds under study (n=7). Recovery values ranged from 72 to 118% with CV ≤ 20%, for veterinary drugs, and 71 to 120% with RSD ≤ 21%, for pesticides. The detection and quantification limits of the method were 1.5 and 5 µg kg-1 , respectively. The developed method proved to be suitable for the determination of 168 substances in animal feed and can be used for regulatory and monitoring purposes.